Penerapan Diferensiasi Kurikulum Inklusif dalam Menghadapi Tantangan Emosional Siswa Sekolah Dasar - Asna Istikmalatul Muktamaroh; Dwi Rahmi Anissa Tanjung; Haya Sabila Aulia Br Munthe; Sekar Melati Pasaribu; Sazkyla Nur Efendi; Nesa Andari (Jurnal Keluarga Sehat Sejahtera, 2026)
Inclusive education is an effort to provide equitable educational services for all students, including those with special needs. In practice, elementary school teachers face increasingly complex challenges, particularly in managing the diversity of learning needs and emotional dynamics of students. Emotional challenges such as anxiety, low self-confidence, difficulty controlling emotions, and barriers to social interaction can impact the learning process. One approach deemed relevant to address these challenges is Differentiated Inclusive Curriculum (DIKSI). This study aims to analyze the application of DIKSI in helping teachers address students' emotional challenges in elementary schools and identify obstacles that arise in its implementation. The study used a qualitative approach with a literature review. Data were obtained through documentation of 11 scientific reference sources, consisting of 6 national journals and 5 international journals published between 2023 and 2026. Data were analyzed descriptively through data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of DIKSI can adapt learning based on students' learning readiness, interests, learning profiles, and individual needs. This approach has resulted in increased learning motivation, active participation, self-confidence, social interaction skills, and the creation of an emotionally safe learning environment. However, the implementation of DIKSI still faces obstacles such as a lack of teacher understanding, limited time, limited facilities, large student numbers, and suboptimal school support. Therefore, DIKSI can be an effective strategy to support inclusive learning while also helping teachers manage students' emotional challenges in elementary schools.